Menedzsment szakos hallgatók a munkaerőpiacon: az elhelyezkedés mintázatai - Fónai, Mihály (International Journal of Engineering and Management Sciences, 2016)
The present study analyses the labour market career of graduates from three management majors. Majors in connection with the economic and engineering educational field (economy and management, engineering manager, human resources manager) belong to the average and in numerous aspects to the good status majors and professions. The social recrutation of the majors analysed is middleclass. According to their  labour market success, such as the duration of finding a job, the level of employment and income they are among professions of favourable position. The knowledge gained at university may be considered well usable in their work. Their satisfaction with the different components of their work is similar to other university graduates, they are most satisfied with the content of their work, and less with its prestige and possible income.In this study we analyse 2011 and 2012 databases of the Graduate Tracking System.